A global perspective on the management and outcomes of peripartum cardiomyopathy: a systematic review and meta‐analysis. (26th July 2022) - Hoevelmann, Julian; Engel, Mark E.; Muller, Elani; Hohlfeld, Ameer; Böhm, Michael; Sliwa, Karen; Viljoen, Charle
Abstract : Aims: Peripartum cardiomyopathy (PPCM) remains a major contributor to maternal morbidity and mortality worldwide. The disease is associated with various complications occurring mainly early during its course. Reported adverse outcomes include decompensated heart failure, thromboembolic complications, arrhythmias and death. We sought to systematically and comprehensively review published literature on the management and outcome of women with PPCM across different geographical regions and to identify possible predictors of adverse outcomes. Methods and results: We performed a comprehensive search of relevant literature (2000 to June 2021) across a number of electronic databases. Cohort, case‐control and cross‐sectional studies, as well as control arms of randomized controlled trials reporting on 6‐ and/or 12‐month outcomes of PPCM were considered eligible (PROSPERO registration: CRD42021255654). Forty‐seven studies (4875 patients across 60 countries) met the inclusion criteria. Haemodynamic and echocardiographic parameters were similar across all continents. All‐cause mortality was 8.0% (95% confidence interval [CI] 5.5–10.8, I 2  = 79.1%) at 6 months and 9.8% (95% CI 6.2–14.0, I 2  = 80.5%) at 12 months. All‐cause mortality was highest in Africa and Asia/Pacific. Overall, 44.1% (95% CI 36.1–52.2, I 2  = 91.7%) of patients recovered their left ventricular (LV) function within 6 months and 58.7% (95% CI 48.1–68.9, I 2  = 75.8%) within 12 months. Europe and North America reported the highest prevalence of LV recovery. Frequent prescription of beta‐blocker, angiotensin‐converting enzyme inhibitor/angiotensin receptor blocker and bromocriptine/cabergoline were associated with significantly lower all‐cause mortality and better LV recovery. Conclusion: We identified significant global differences in 6‐ and 12‐month outcomes in women with PPCM. Frequent prescription of guideline‐directed heart failure therapy was associated with better LV recovery and lower all‐cause mortality. Timely initiation and up‐titration of heart failure therapy should therefore be strongly encouraged to improve outcome in PPCM. Abstract : There are regional differences in both all‐cause mortality and left ventricular (LV) recovery in peripartum cardiomyopathy. These differences may be explained by the variable prescription of guideline‐directed medical therapy and access to health care services in different parts of the world. Studies that reported high prescription rates of beta‐blockers, angiotensin‐converting enzyme inhibitors/angiotensin receptor blockers, and bromocriptine/cabergoline were associated with better rates of LV recovery and lower all‐cause mortality.